Charlie Parker: Dark Hollow - Book 2 - Connolly, John 1968- (New York : Emily Bestler Books/Atria, 2015)
Charlie Parker, a former New York City detective with a haunted past, befriends a down-and-out mother with a small child. When she turns up dead, Charlie's first suspect is her estranged husband. Charlie follows the man's trail to Maine and there he becomes entangled in a series of strange occurances which all seem to harken back to a string of unsolved murders that took place generations before. The murders were never solved and now Charlie must hunt for a killer and the connection between two crimes that span a century.
Keywords: Parker, Charlie "Bird" (Fictitious character) -- Fiction; Private investigators -- Fiction -- New York (State); Serial murders -- Fiction; Ex-police officers -- Fiction; Ex-police officers; Parker, Charlie "Bird" (Fictitious character); Private Investigators; Serial murders; New York (N.Y.) -- Fiction; Scarborough (Me.) -- Fiction; Maine; New York (State) -- New York; Fiction; Detective and mystery fiction